Current trends in the development of molecularly imprinted polymers in CEC - Mu, Li-Na; Wei, Ze-Hui; Liu, Zhao-Sheng (Electrophoresis, 2015)
This review focused on the developments in the field of molecularly imprinted polymers (MIPs) for CEC since 2009. New preparation techniques of MIP‐based CEC, such as, portable microchip with macroporous monolithic imprinted microchannel, and low cross‐linking MIPs based on liquid crystalline monomers, were discussed. Using selected cases rather than a comprehensive review of the entire field, our goal is to highlight the studies of the interest with an emphasis on recent work, and offers suggestions for future development in the field of imprinted materials for CEC separation.